2008
DOI: 10.1007/s00441-007-0561-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a gelsolin-related protein in spermatogenesis of the earthworm Lumbricus terrestris

Abstract: A gelsolin-related protein was isolated from seminal vesicles of the annelid Lumbricus terrestris. Compared with the isoforms of the gelsolin-related protein previously found in the muscle of the annelid body wall, the isolated protein was assigned to the first isoform (EWAM-P1) because of its electrophoretic mobility, chromatographic elution behaviour, immunological cross-reactivity and identical nucleotide sequence of segments obtained by reverse transcription/polymerase chain reaction. Immunofluorescence st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Simultaneously dividing germ cells have repeatedly been observed during spermatogenesis ( Fig. 2a- d;Fernández et al 1992;Krüger et al 2008). In female cysts, the synchrony of mitoses may be lost at different phases of their development, as observed in T. tessulatum and P. geometra (this study; not shown).…”
Section: Cystocyte Mitotic Divisions and Orientation Of Mitotic Spindlesmentioning
confidence: 61%
See 3 more Smart Citations
“…Simultaneously dividing germ cells have repeatedly been observed during spermatogenesis ( Fig. 2a- d;Fernández et al 1992;Krüger et al 2008). In female cysts, the synchrony of mitoses may be lost at different phases of their development, as observed in T. tessulatum and P. geometra (this study; not shown).…”
Section: Cystocyte Mitotic Divisions and Orientation Of Mitotic Spindlesmentioning
confidence: 61%
“…The testes in Clitellates contain clusters of gonial cells (cystocytes). In leeches (Hirudinea), spermatogenesis is confined to male gonads (Fernández et al 1992), whereas in oligochaetous clitellates, cystocyte clusters still at the initial stages of their differentiation are transferred from testes into seminal vesicles in which the germ cells undergo further divisions, enter meiosis and then pass through the subsequent phases of spermiogenesis (Ferraguti 1999;Jamieson 2006;Krüger et al 2008). Development of the male germ-cell clusters is not synchronous and so clusters at various stages of mitotic divisions, meiosis and spermiogenesis can be observed (Fernández et al 1992;Ferraguti 1999;Jamieson 2006; this study).…”
Section: Gross Morphology Of Clitellate Reproductive System and Organmentioning
confidence: 97%
See 2 more Smart Citations
“…These cysts have a characteristic spatial arrangement; each germ cell in a given cyst has only one RC connecting it to a common anuclear cytoplasmic mass -the cytophore. Numerous studies have shown that the formation of germline cysts with a central cytophore is a conserved phase of gametogenesis in Clitellata (Fernández et al, 1992;Ferraguti, 1999;Jamieson, 2006;Krüger et al, 2008;Spałek-Wołczyńska et al, 2008;Swiątek, 2005bSwiątek, , 2008Świątek et al, 2009Ben Ahmed et al, 2010) and should be regarded as a primary condition (Urbisz et al, 2010;Świątek et al, 2012). Similar germline cysts with a central cytoplasmic mass have been found during gametogenesis in some Polychaeta, Plathyhelmintes and Nematoda (Sawada, 1975;Hirsh et al, 1976;Foor, 1983;Gibert et al, 1984;Sopott-Ehlers, 1989).…”
Section: Germline Cystsmentioning
confidence: 97%